Morphological Character and Percentage of Hotate Clams (Patinopecten Yessoensis) Meat Weight in the Growing Phase, in Funka Bay, Hokkaido, Japan. - faza; Hary Tjahja Soedibya, Petrus; Listiowati, Emyliana; Gyogyo, Iriyama (PT. Artha GenetikaLab Indonesia, 2023)
This study focuses on the growth and meat weight percentage of Hotate clams (Patinopecten yessoensis) during the rearing phase in Funka Bay, Hokkaido, Japan. Japan, as a major producer of seafood, including Hotate clams, plays a significant role in global seafood consumption. The objective of this study was to analyze the length-weight relationship of Hotate scallops and assess their meat weight percentage during the rearing phase. The research method involved observations using a random sampling technique during the period from August to October 2022. Samples were taken in Funka Bay, with coordinates between 42°20'-42°40' North and 140°00'-141°00' East at a depth of 43 meters. Results showed that the length-weight relationship of Hotate clams during August to October exhibited a negative allometric growth pattern, with the highest constant reaching 2.640. This means that length growth is faster than body weight. The percentage of Hotate clam (P. yessoensis) meat weight during the rearing phase ranged from 31.03% to 35.70%. This study provides important insights into the growth and meat composition of Hotate clams during critical phases in their culture in Funka Bay, Hokkaido, Japan. It can serve as a valuable information foundation for the management and maintenance of sustainable and productive Hotate clam aquaculture in the future.